AI & Accessibility: A Conceptual Framework for Inclusive Technology - Laxminarayana Korada (International Journal of Intelligent Systems and Applications in Engineering, 2024)
This paper presents a framework that synthesizes artificial intelligence (AI) with established accessibility principles to facilitate the development of inclusive technologies. The primary objective is to ensure that individuals with disabilities can leverage AI-driven systems to enhance their learning, employment, and social interactions. We delineate the intersection of AI's capabilities with universal design concepts, underscoring the necessity for technology that is both adaptable and configurable to meet diverse needs. The proposed framework outlines standards for legislators and developers, advocating the creation of AI applications specifically tailored to assist individuals with disabilities. Furthermore, this study addresses critical ethical considerations, including data privacy and informed consent, which are imperative for the implementation of accessible technology. This paper explores these themes in depth.